Kerosakan dan kemerosotan struktur konkrit di Malaysia - Mokhtar, Mohd. Zaki (2006)
Concrete is foremost among the construction material used in civil engineering practice in Malaysia. The reasons of its applicable usage are the economic and the minimal maintenance requirement during service. However concrete has been facing several damage and deterioration during its life time due to lack of knowledge in concrete behaviour. This project was conducted to study the types of concrete structure problems specifically in Malaysia. The main data was gathered from Public Work Department of Malaysia and some other data were from IKRAM Research Center, Local Authority, and some other more were through other agencies. From this survey, the major cause of the concrete damage was deterioration of concrete (39%) which contributed the highest numbers of defective concrete case, followed by geotechnical error (19%), construction error (17%), unpredictable factors (13%) and design deficiency (12%) respectively. The major factor for concrete deterioration is carbonation (85%), chloride attack (9%), sulphate attack (3%) and alkali attack (3%) respectively.